Neodymium iron boron magnet material, its manufacturing method and applications
By optimizing the composition and incorporating a NbxCoy phase in the grain boundary phase, the neodymium iron boron magnet materials achieve improved coercive force and residual magnetic flux density, addressing the limitations of existing magnets.
Patent Information
- Application Number
- JP2023544213
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-29
- Filing Date
- 2022-01-17
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2042-01-17
AI Technical Summary
Existing neodymium iron boron magnet materials face issues with poor magnetic properties, particularly in coercive force and residual magnetic flux density, despite improvements aimed at enhancing these properties.
Optimizing the composition of neodymium iron boron magnets by adjusting the content of elements such as R, Al, Cu, Co, B, and Nb, and incorporating a NbxCoy phase in the grain boundary phase to improve coercive force while maintaining high residual magnetic flux density and squareness ratio.
The optimized composition significantly enhances coercive force and maintains high residual magnetic flux density and squareness ratio, outperforming conventional technologies.
Smart Images

Figure 0007600416000001 
Figure 0007600416000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a neodymium iron boron magnet material, its manufacturing method and applications. [Background technology]
[0002] Permanent magnet materials are being developed as important materials that support electronic devices. RTB-based permanent magnet materials are known to have the highest performance among permanent magnets, and are used in voice coil motors for hard disk drives, motors for electric vehicles, motors for industrial equipment, etc.
[0003] How to improve the overall properties of RTB permanent magnet materials is currently a trend being explored in this field. For example, Chinese patent document CN110993233A discloses an RTB permanent magnet material, which increases the content of X(Al\Cu\Ga) and adjusts the content of rare earths to change the ratio of Fe and B, thereby producing a 6:13:1 phase even with the conventional content of B, thereby obtaining a magnet material with excellent magnetic properties.
[0004] Further, for example, Chinese patent document CN111180159A also discloses a neodymium iron boron permanent magnet material, and a specific embodiment of the patent discloses a magnet material having the following composition and structure: 29 wt.% Nd, 0.1 wt.% Tb, 0.4 wt.% Dy, 0.4 wt.% Cu, 0.5 wt.% Al, 0.9 wt.% Co, 1 wt.% B, 0.25 wt.% Nb, and 67.45 wt.% Fe, and the intergranular rare earth rich phase further generates a specific mass ratio phase: Tb0.4Dy2.5-Al0.59-Nd89.6-Cu1.4-Co5.1.
[0005] The above components are all improvements based on high Cu and high Al magnet materials, mainly because the addition of Cu element effectively improves the coercive force of NdFeB magnets, but too much Cu (e.g., more than 0.35wt.%) will cause microcracks to form after magnet sintering due to enrichment at grain boundaries, which will reduce the density and strength of the magnet, and the prior art generally solves the above defects by adding Al (e.g., Chinese patent document CN110993234A). However, the coercive force and residual magnetic flux density of these magnet materials still have a certain difference from the theoretical values of permanent magnet materials.
[0006] Further optimizing the components of the magnetic material to obtain a NdFeB magnetic material with higher overall properties of coercivity and residual magnetic flux density is a technical challenge that needs to be solved as soon as possible. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention provides a NdFeB magnet material and its manufacturing method and application, mainly to overcome the defects of the low magnetic properties of the Al and Cu-containing NdFeB magnet material in the prior art. The present invention further optimizes the components of the NdFeB magnet material, significantly improving the coercive force of the produced NdFeB magnet material while maintaining high remanence and squareness ratio. [Means for solving the problem]
[0008] The present invention mainly solves the above technical problems through the following technical ideas.
[0009] The present invention provides a neodymium iron boron magnet material, the neodymium iron boron magnet material comprising the following components: R: 28 to 33 wt.%, wherein R is a rare earth element; The R contains Nd, the Nd content being 27 to 31.5 wt.%, Al: 0.30-1.3 wt.%, Cu: 0.35-0.6wt.%, 0 <Co≦0.74wt.%、 B: 0.98-1.2 wt.%, Fe: 62-69 wt.%, where wt.% means the percentage of the mass of each component relative to the total mass of the NdFeB magnet material; The neodymium iron boron magnet material contains Nb, and the mass content of Nb satisfies the condition: (Pr+Co)wt.%≦(1+Nb)wt.%.
[0010] In the present invention, the content of R is preferably 29 to 32.5 wt.%, for example, 29.3 wt.%, 29.5 wt.%, 29.7 wt.%, 30.5 wt.%, 30.6 wt.%, 31.3 wt.%, 31.4 wt.%, 31.9 wt.%, 32 wt.%, or 32.3 wt.%, where wt.% means the percentage of the total mass of the NdFeB magnet material.
[0011] In the present invention, the Nd content is preferably 27.5 to 31 wt.%, for example, 28.3 wt.%, 28.9 wt.%, 29.1 wt.%, 29.3 wt.%, 29.5 wt.%, 29.7 wt.%, 29.8 wt.%, 30.2 wt.%, 30.5 wt.% or 30.7 wt.%, where wt.% means the percentage of the total mass of the Nd iron boron magnet material.
[0012] In the present invention, the Pr content is preferably 0 to 0.3 wt.%, for example, 0.1 wt.% or 0.2 wt.%, where wt.% means the percentage of the total mass of the NdFeB magnet material.
[0013] In the present invention, as will be understood by those skilled in the art, the above (Pr+Co)wt.%≦(1+Nb)wt.% generally means that the sum of the mass percentage of Pr and the mass percentage of Co in the NdFeB magnet material is less than or equal to the sum of the mass percentage of Nb and 1wt.%.
[0014] In the present invention, the total content of Pr and Co is preferably 0.9 wt.% or less, but not 0 wt.%, for example, 0.25 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.% or 0.8 wt.%, where wt.% means the percentage of the total mass of the NdFeB magnet material.
[0015] In the present invention, the NdFeB magnet material preferably further contains RH, and the RH is a heavy rare earth element.
[0016] Here, the content of RH can be a content that is common in this field, and is preferably 0.5-3 wt.%, for example, 0.6 wt.%, 0.9 wt.%, 1 wt.%, 1.2 wt.%, 1.4 wt.%, 1.5 wt.%, 1.7 wt.%, 2 wt.%, 2.3 wt.% or 2.5 wt.%, where wt.% means the percentage of the total mass of the NdFeB magnet material.
[0017] Here, the type of RH can be any conventional one in the art, and is preferably Dy and / or Tb.
[0018] When the RH contains Dy, the content of Dy is preferably 0.2 to 2.5 wt.%, for example, 0.9 wt.%, 1.4 wt.%, 1.5 wt.%, 1.7 wt.%, or 2.3 wt.%, where wt.% means the percentage of the total mass of the NdFeB magnet material.
[0019] When the RH contains Tb, the content of Tb is preferably 0.5 to 2.5 wt.%, for example, 0.6 wt.%, 1.2 wt.%, or 2 wt.%, where wt.% means the percentage of the total mass of the NdFeB magnet material.
[0020] In the present invention, the Nb content is preferably 0.25 to 0.6 wt.%, for example, 0.26 wt.%, 0.3 wt.%, 0.35 wt.%, or 0.55 wt.%, where wt.% means the percentage of the total mass of the NdFeB magnet material.
[0021] In the present invention, the Al content is preferably 0.45 to 1.2 wt.%, for example, 0.46 wt.%, 0.61 wt.%, 0.65 wt.%, 0.7 wt.%, or 1.15 wt.%, where wt.% means the percentage of the total mass of the NdFeB magnet material.
[0022] In the present invention, the Cu content is preferably 0.35 to 0.45 wt.%, for example, 0.36 wt.%, 0.37 wt.%, 0.38 wt.%, 0.39 wt.%, 0.4 wt.%, or 0.42 wt.%, where wt.% means the percentage of the total mass of the NdFeB magnet material.
[0023] In the present invention, the Co content is preferably 0.7 wt.% or less, but not 0 wt.%, for example, 0.2 wt.%, 0.25 wt.%, 0.5 wt.% or 0.6 wt.%, where wt.% means the percentage of the total mass of the NdFeB magnet material.
[0024] In the present invention, the B content is preferably 0.98 to 1.05 wt.%, for example, 0.99 wt.%, 1 wt.%, 1.01 wt.%, or 1.02 wt.%, where wt.% means the percentage of the total mass of the neodymium iron boron magnet material.
[0025] In the present invention, the Fe content is preferably 64 to 68 wt.%, for example, 64.34 wt.%, 65.07 wt.%, 65.22 wt.%, 65.33 wt.%, 65.75 wt.%, 65.85 wt.%, 65.91 wt.%, 66.31 wt.%, 66.83 wt.%, 66.98 wt.%, 67.64 wt.%, 67.74 wt.%, 67.84 wt.%, 67.94 wt.% or 67.95 wt.%, where wt.% means the percentage of the total mass of the NdFeB magnet material.
[0026] In the present invention, the NdFeB magnet material preferably contains a NbxCoy phase, where the total molar amount of Nb and Co in the NbxCoy phase is 100%, x is 30-40%, y is 60-70%, the NbxCoy phase is located in a grain boundary phase, and the ratio of the area of the NbxCoy phase to the total area of the grain boundary phase is 3-6%, where x and y in the NbxCoy phase respectively represent the molar amount of Nb or Co and the percentage of the total molar amount of "Nb and Co".
[0027] In the present invention, the area of the NbxCoy phase or the total area of the grain boundary phase generally means the area occupied by the vertically oriented surface of the NdFeB magnet material detected during FE-EPMA detection.
[0028] Here, x is, for example, 32%, 33%, 34%, 35% or 39%.
[0029] Here, y is, for example, 61%, 62%, 65%, 66%, 67% or 68%.
[0030] In the present invention, the ratio of the area of the NbxCoy phase to the total area of the grain boundary phase is preferably 4 to 4.5%, for example, 4.1%, 4.2%, 4.3% or 4.4%.
[0031] The inventors presumed that a certain content of the NbxCoy phase exists in the grain boundary phase, which can pin the grain boundaries and more significantly inhibit the growth of crystal grains, thereby improving the coercivity of the NdFeB magnet.
[0032] In the present invention, the above-mentioned grain boundary phase may have the meaning commonly understood in the art, and is generally a general term for a region formed by a two-grain grain boundary phase and an intergranular triangular region. The two-grain grain boundary phase is generally a grain boundary phase between two main phase grains.
[0033] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 29.7wt.% Nd, 1.7wt.% Dy, 0.61wt.% Al, 0.4wt.% Cu, 0.6wt.% Co, 0.25wt.% Nb, 0.99wt.% B and 65.75wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NdFeB magnet material includes a Nb35Co65 phase, and the ratio of the area of the Nb35Co65 phase to the total area of the grain boundary phase is 4.5%.
[0034] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 29.8wt.% Nd, 0.1wt.% Pr, 1.4wt.% Dy, 0.46wt.% Al, 0.38wt.% Cu, 0.7wt.% Co, 0.25wt.% Nb, 1wt.% B and 65.91wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NbFeB magnet material includes a Nb35Co65 phase, and the ratio of the area of the Nb35Co65 phase to the total area of the grain boundary phase is 4.4%.
[0035] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 30.2wt.% Nd, 1.7wt.% Dy, 0.61wt.% Al, 0.38wt.% Cu, 0.6wt.% Co, 0.3wt.% Nb, 0.99wt.% B and 65.22wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NdFeB magnet material includes a Nb39Co61 phase, and the ratio of the area of the Nb39Co61 phase to the total area of the grain boundary phase is 4.5%.
[0036] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 29.3wt.% Nd, 0.3wt.% Pr, 2.3wt.% Dy, 0.61wt.% Al, 0.39wt.% Cu, 0.5wt.% Co, 0.26wt.% Nb, 1.01wt.% B and 65.33wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NbFeB magnet material includes a Nb33Co67 phase, and the ratio of the area of the Nb33Co67 phase to the total area of the grain boundary phase is 4.3%.
[0037] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 30.7wt.% Nd, 0.1wt.% Pr, 1.5wt.% Dy, 1.15wt.% Al, 0.37wt.% Cu, 0.6wt.% Co, 0.25wt.% Nb, 0.99wt.% B and 64.34wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NbFeB magnet material includes a Nb35Co65 phase, and the ratio of the area of the Nb35Co65 phase to the total area of the grain boundary phase is 4.4%.
[0038] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 28.9 wt.% Nd, 0.6 wt.% Tb, 0.46 wt.% Al, 0.36 wt.% Cu, 0.5 wt.% Co, 0.26 wt.% Nb, 0.98 wt.% B and 67.94 wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NdFeB magnet material includes a Nb39Co61 phase, and the ratio of the area of the Nb39Co61 phase to the total area of the grain boundary phase is 4.5%.
[0039] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 28.3wt.% Nd, 1.2wt.% Tb, 0.45wt.% Al, 0.35wt.% Cu, 0.5wt.% Co, 0.26wt.% Nb, 0.99wt.% B and 67.95wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NdFeB magnet material includes a Nb34Co66 phase, and the ratio of the area of the Nb34Co66 phase to the total area of the grain boundary phase is 4.5%.
[0040] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 27wt.% Nd, 0.2wt.% Pr, 2.5wt.% Tb, 0.45wt.% Al, 0.36wt.% Cu, 0.5wt.% Co, 0.26wt.% Nb, 0.99wt.% B and 67.74wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NdFeB magnet material includes a Nb35Co65 phase, and the ratio of the area of the Nb35Co65 phase to the total area of the grain boundary phase is 4.4%.
[0041] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 27.5wt.% Nd, 2wt.% Tb, 0.45wt.% Al, 0.36wt.% Cu, 0.6wt.% Co, 0.26wt.% Nb, 0.99wt.% B and 67.84wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NdFeB magnet material includes a Nb35Co65 phase, and the ratio of the area of the Nb35Co65 phase to the total area of the grain boundary phase is 4.3%.
[0042] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 28.3wt.% Nd, 0.1wt.% Pr, 0.9wt.% Dy, 0.7wt.% Al, 0.42wt.% Cu, 0.7wt.% Co, 0.25wt.% Nb, 0.99wt.% B and 67.64wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NbFeB magnet material includes a Nb35Co65 phase, and the ratio of the area of the Nb35Co65 phase to the total area of the grain boundary phase is 4.4%.
[0043] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 30.5wt.% Nd, 1.5wt.% Dy, 0.65wt.% Al, 0.45wt.% Cu, 0.6wt.% Co, 0.25wt.% Nb, 0.98wt.% B and 65.07wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NdFeB magnet material includes a Nb32Co68 phase, and the ratio of the area of the Nb32Co68 phase to the total area of the grain boundary phase is 4.3%.
[0044] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 29.7wt.% Nd, 1.7wt.% Dy, 0.61wt.% Al, 0.4wt.% Cu, 0.5wt.% Co, 0.25wt.% Nb, 0.99wt.% B and 65.85wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NdFeB magnet material includes a Nb33Co67 phase, and the ratio of the area of the Nb33Co67 phase to the total area of the grain boundary phase is 4.3%.
[0045] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 29.1wt.% Nd, 1.5wt.% Tb, 0.46wt.% Al, 0.37wt.% Cu, 0.25wt.% Co, 0.35wt.% Nb, 0.99wt.% B and 66.98wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NdFeB magnet material includes a Nb39Co61 phase, and the ratio of the area of the Nb39Co61 phase to the total area of the grain boundary phase is 4.2%.
[0046] In one preferred embodiment of the present invention, the NdFeB magnet material is composed of 29.5wt.% Nd, 0.2wt.% Dy, 0.8wt.% Tb, 0.46wt.% Al, 0.37wt.% Cu, 0.25wt.% Co, 0.55wt.% Nb, 1.04wt.% B and 66.83wt.% Fe, where wt.% means the percentage of the mass of each component to the total mass of the NdFeB magnet material, and the grain boundary phase of the NdFeB magnet material includes a Nb40Co60 phase, and the ratio of the area of the Nb40Co60 phase to the total area of the grain boundary phase is 4.1%.
[0047] The present invention further provides a method for producing a neodymium iron boron magnet material, the method comprising the steps of preparing raw materials of each component according to the components of the neodymium iron boron magnet material, and then melting, casting, crushing, molding, sintering and aging the mixture of the raw materials of each component in order;
[0048] The aging treatment includes a three-stage aging treatment, in which the first stage aging treatment is performed at a temperature of 850 to 950°C, the second stage aging treatment is performed at a temperature of 650 to 700°C, and the third stage aging treatment is performed at a temperature of 450 to 550°C.
[0049] In the present invention, the temperature of the first stage aging treatment is preferably 870 to 890°C, for example, 880°C.
[0050] In the present invention, the time for the first stage aging treatment may be 2 to 4 hours, and is, for example, 3 hours.
[0051] In the present invention, the temperature of the second stage aging treatment is preferably 660 to 690°C, for example, 670°C or 680°C.
[0052] In the present invention, the time period of the second stage aging treatment is preferably 1 to 4 hours, for example, 2 hours.
[0053] In the present invention, the temperature of the third stage aging treatment is preferably 480 to 500°C, for example, 490°C.
[0054] In the present invention, the time period of the third stage aging treatment is preferably 1 to 4 hours, for example, 3 hours.
[0055] In the present invention, after the third stage aging treatment, a grain boundary diffusion treatment can be further carried out.
[0056] Here, the temperature of the grain boundary diffusion treatment is preferably 850 to 1000°C, for example, 900°C, 910°C, or 920°C.
[0057] Here, the time for the grain boundary diffusion treatment is preferably 10 to 30 hours, for example, 20 hours.
[0058] Here, the diffusion source for the grain boundary diffusion treatment is preferably a Dy metal powder and / or an alloy containing Dy.
[0059] The mass percentage of the diffusion source relative to the total mass of the neodymium iron boron magnet material is preferably 0.3 to 0.5 wt.%, for example 0.4 wt.%.
[0060] In the present invention, the smelting process can be a typical smelting process in this field.
[0061] Here, the degree of vacuum in the melting and smelting is, for example, 5×10 −2 Pa.
[0062] Here, the temperature of the melting and smelting is, for example, 1550°C or lower, for example, 1540°C.
[0063] In the present invention, the casting process can be a conventional casting process in this field.
[0064] Here, the casting process employs, for example, a strip casting method.
[0065] Here, the casting temperature may be 1390 to 1460°C, for example, 1410°C.
[0066] Here, the thickness of the alloy flakes obtained after the casting may be 0.25 to 0.40 mm.
[0067] In the present invention, the grinding process can be a conventional grinding process in this field.
[0068] Here, the pulverization is generally carried out in the order of hydrogen pulverization and jet mill pulverization.
[0069] The hydrofractionation process generally involves sequentially carrying out hydrogen absorption, dehydrogenation and cooling treatments.
[0070] The hydrogen absorption can be carried out under a hydrogen pressure condition of 0.085 MPa.
[0071] The dehydrogenation can be carried out under conditions of evacuation and heating. The dehydrogenation temperature may be 480 to 520°C, and is, for example, 500°C.
[0072] The gas atmosphere during the jet mill pulverization may have an oxidizing gas content of 100 ppm or less, and the oxidizing gas content means the content of oxygen and / or moisture.
[0073] After the jet mill pulverization, a lubricant such as zinc stearate is generally further added. The amount of the lubricant added may be 0.05 to 0.15% of the powder mass obtained after the jet mill pulverization, for example, 0.12%.
[0074] In the present invention, the molding may be performed by a magnetic field molding method.
[0075] Here, the magnetic field molding can be carried out at a magnetic field strength of, for example, 1.8 to 2.5T.
[0076] In the present invention, the sintering process can be a conventional sintering process in this field.
[0077] Here, the sintering temperature may be 1000 to 1100°C, for example, 1080°C.
[0078] Here, the sintering time may be 4 to 8 hours, for example, 6 hours.
[0079] The present invention further provides a neodymium iron boron magnet material, which is produced by the above-mentioned production method.
[0080] The present invention further provides the application of the above-mentioned NdFeB magnet material as electronic components.
[0081] By arbitrarily combining the above-mentioned respective preferred conditions in accordance with the common general knowledge in this field, each preferred embodiment of the present invention can be obtained.
[0082] All of the reagents and raw materials used in the present invention are commercially available. Effect of the Invention
[0083] The positive and progressive effect of the present invention is that, in the NdFeB magnetic material containing Al and Cu, the contents of elements such as Co, Al, Cu, Pr and Nb are further optimized, so that the coercive force of the obtained NdFeB magnetic material is significantly improved, while the residual magnetic flux density and squareness ratio also remain at high levels. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0084] The present invention will be further described below by way of examples, but the present invention is not limited to the scope of the above examples. In the following examples, the experimental methods for which no specific conditions are specified are selected according to the usual methods and conditions or according to the product specifications. Example 1
[0085] Neodymium Iron Boron Magnet Material Production: (1) Melting and smelting: The raw materials prepared according to the components of the neodymium iron boron magnet material in Table 1 were placed in a high-frequency vacuum induction melting furnace with a vacuum degree of 5×10-2 Pa, and the molten liquid was melted and smelted at 1540℃. (2) Casting: Rapid solidification casting method is adopted to obtain alloy flakes (thickness 0.29 mm), and the casting temperature is 1410℃. (3) Crushing: Hydrocrushing and jet mill crushing are performed in that order.
[0086] Hydrogen crushing is a process that involves hydrogen absorption, dehydrogenation, and cooling. Hydrogen absorption is performed under hydrogen pressure conditions of 0.085 MPa. Dehydrogenation is performed under conditions of evacuation and heating, and the dehydrogenation temperature is 500°C.
[0087] Jet mill pulverization is performed with an oxidizing gas content of 100 ppm or less, and the particle size obtained by pulverization is 4.2 μm, where oxidizing gas means oxygen or water content. The pressure in the grinding chamber for jet mill pulverization is 0.68 MPa. After pulverization, zinc stearate is added as a lubricant, and the amount added is 0.12% of the powder weight after mixing.
[0088] (4) Magnetic field molding: This is carried out under the protection of a magnetic field strength of 1.8 to 2.5 T and a nitrogen atmosphere.
[0089] (5) Sintering: Sinter and cool under vacuum conditions of 5×10-3 Pa. Sinter at 1080℃ for 6 hours, and before cooling, pass Ar gas through to make the air pressure reach 0.05 MPa.
[0090] (6) Three-stage aging: the first stage aging temperature is 880℃, the time is 3h, the second stage aging temperature is 680℃, the time is 2h, and the third stage aging temperature is 490℃, the time is 3h.
[0091] (7) Grain boundary diffusion treatment: By the grain boundary diffusion treatment, Dy metal powder (the content of Dy added is 0.4 wt.%, where wt.% is the percentage of the total mass of the NdFeB magnet material, and the remaining Dy content of 1.3 wt.% listed in Table 1 is added during melting and smelting) is diffused into the magnet material obtained after the three-stage aging treatment, and the temperature of the grain boundary diffusion treatment is 910°C, and the time is 20 hours.
[0092] In Examples 1 to 5 and 10 to 12 and Comparative Examples 1 to 6, raw materials were prepared with the components shown in Table 1 below, the second stage aging temperature was as shown in Table 1, and the other manufacturing steps were the same as in Example 1. Here, the content of Dy added during grain boundary diffusion was 0.4 wt.% in all cases, and the remaining Dy in Table 1 was added during melting and smelting.
[0093] In Examples 6 to 9, 13, and 14, raw materials were prepared with the components shown in Table 1 below, and the manufacturing process was the same as Example 1, with no grain boundary diffusion treatment being performed after the third stage aging treatment, and the temperature of the second stage aging treatment being as shown in Table 1 below. Effect Example 1
[0094] 1. Component measurement: The neodymium iron boron magnets in Examples 1 to 14 and Comparative Examples 1 to 6 were measured using an inductively coupled plasma optical emission spectrometer (ICP-OES). The detection results are shown in Table 1 below.
[0095] (Table 1) (Unit: wt.%, the percentage of each element in the total mass of the neodymium iron boron magnet material) JPEG0007600416000001.jpg159161
[0096] Note: " / " indicates that the element is not added and not detected. "Y" means positive and "N" means negative. The values of Fe content of the NdFeB magnet materials in the above examples and comparative examples are 100% minus the content of each element, and it is known to those skilled in the art that the Fe content contains some unavoidable impurities introduced during the manufacturing process.
[0097] 2. Magnetic property test The NdFeB magnet materials in Examples 1 to 14 and Comparative Examples 1 to 6 were measured using a PFM pulse type BH demagnetization curve test equipment, the measurement temperature was 20°C, and data on residual magnetic flux density (Br), intrinsic coercivity (Hcj), maximum energy product (BHmax), and squareness ratio (Hk / Hcj) were obtained, and the detection results are shown in Table 2 below.
[0098] 3. Microstructural features Detection by FE-EPMA: The vertically oriented surface of the NdFeB magnet material in Examples 1 to 14 and Comparative Examples 1 to 6 was polished and detected by adopting a field emission electron probe microanalyzer (FE-EPMA) (JEOL, 8530F). First, the distribution of Nb and Co elements in the grain boundary phase of the NdFeB magnet material was identified by FE-EPMA surface scanning, and then the molar content of Nb and Co in the NbxCoy phase was identified by FE-EPMA single point quantitative analysis, and the measurement conditions were an acceleration voltage of 15 kv and a probe beam current of 50 nA. The detection results are shown in Table 2 below.
[0099] Here, the proportion of the area of the NbxCoy phase is the ratio of the area of the NbxCoy phase in a cross section (the above-mentioned vertically oriented surface) where the neodymium iron boron magnet material is detected to the total area of the grain boundary phase in the cross section.
[0100] [Table 2]
[0101] Note: The subscripts for NbxCoy phase in the table omit the %.
[0102] As can be seen from the data in the above table, the present invention adopts a specific three-step aging treatment in the manufacturing process according to the specific content of Co, Al, Cu, Pr, Nb, etc., so that the coercivity of the manufactured NdFeB magnet material is significantly improved compared with the prior art, and at the same time, the remanence and squareness ratio are maintained at a high level. Furthermore, the microscopic detection results show that the optimized components of the NdFeB magnet material of the present invention form a specific content of NbxCoy phase in the grain boundary phase after being manufactured into the NdFeB magnet material, which can optimize the grain boundary phase and improve the coercivity.
Claims
1. A neodymium iron boron magnet material comprising: R: 28 to 33 wt. %, wherein R is a rare earth element; The R contains Nd, the Nd: 27 to 31.5 wt. %, Al: 0.30-1.3wt. %, Cu: 0.35-0.6wt. %, 0<Co≦0.74wt. %, B: 0.98-1.2wt. %, Fe: 62-69 wt. %, wt. % means the percentage of the mass of each component to the total mass of the neodymium iron boron magnet material; The neodymium iron boron magnet material contains Nb, and the mass content of Nb satisfies the condition of (Pr + Co) wt. % ≦ Nb wt. % + 1 wt. %, The neodymium iron boron magnet material contains a Nb x Co y phase, and x is 30 to 40% and y is 60 to 70% relative to a total molar amount of Nb and Co in the Nb x Co y phase of 100%; The Nb x Co y phase is located in the grain boundary phase, and the ratio of the area of the Nb x Co y phase to the total area of the grain boundary phase is 3-6%, and the area of the Nb x Co y phase or the total area of the grain boundary phase respectively means the area occupied by the vertically oriented surface of the detected NdFeB magnet material. A neodymium iron boron magnet material.
2. The content of R is 29 to 32.5 wt. %, where wt. % means the percentage of the total mass of the NdFeB magnet material; and / or the Nd content is 27.5-31 wt. %, where wt. % means the percentage of the total mass of the Nd-Fe-B magnet material; and / or the Pr content is 0 to 0.3 wt. %, where wt. % means the percentage of the total mass of the NdFeB magnet material; and / or the total content of the Pr and the Co is 0.9 wt. % or less but not 0, where wt. % means a percentage of the total mass of the NdFeB magnet material; and / or the NdFeB magnet material further comprises RH, the RH being a heavy rare earth element; Here, the content of RH is 0.5 to 3 wt. %, where wt. % means the percentage of the total mass of the NdFeB magnet material; Here, the type of RH is Dy and / or Tb, and when RH contains Dy, the content of Dy is 0.2 to 2.5 wt. %, where wt. % means a percentage of the total mass of the NdFeB magnet material; When the RH contains Tb, the content of Tb is 0.5 to 2.5 wt. %, where wt. % means the percentage of the total mass of the NdFeB magnet material.
2. The neodymium iron boron magnet material according to claim 1 .
3. The Nb content is 0.25 to 0.6 wt. %, where wt. % means the percentage of the total mass of the NdFeB magnet material; and / or the content of Al is 0.45-1.2 wt. %, where wt. % means the percentage of the total mass of the NdFeB magnet material; and / or the Cu content is 0.35-0.45 wt. %, where wt. % means the percentage of the total mass of the NdFeB magnet material; and / or the Co content is 0.7 wt. % or less but not 0 wt. %, where wt. % means a percentage of the total mass of the NdFeB magnet material; and / or the content of B is 0.98 to 1.05 wt. %, where wt. % means the percentage of the total mass of the NdFeB magnet material; and / or the Fe content is 64-68 wt. %, where wt. % means the percentage of the total mass of the NdFeB magnet material; 2. The neodymium iron boron magnet material according to claim 1 .
4. wherein x is 32%, 33%, 34%, 35% or 39% and y is 61%, 62%, 65%, 66%, 67% or 68%; The Nb x Co y The phase is located in the grain boundary phase, and the Nb x Co y The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4 to 4.5%. The neodymium iron boron magnet material according to any one of claims 1 to 3.
5. The neodymium iron boron magnet material is composed of 29.7 wt. % Nd, 1.7 wt. % Dy, 0.61 wt. % Al, 0.4 wt. % Cu, 0.6 wt. % Co, 0.25 wt. % Nb, 0.99 wt. % B, and 65.75 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 35 Co 65 The Nb 35 Co 65 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.5%; Alternatively, the neodymium iron boron magnet material is composed of 29.8 wt. % Nd, 0.1 wt. % Pr, 1.4 wt. % Dy, 0.46 wt. % Al, 0.38 wt. % Cu, 0.7 wt. % Co, 0.25 wt. % Nb, 1 wt. % B and 65.91 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 35 Co 65 The Nb 35 Co 65 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.4%; Alternatively, the neodymium iron boron magnet material is composed of 30.2 wt. % Nd, 1.7 wt. % Dy, 0.61 wt. % Al, 0.38 wt. % Cu, 0.6 wt. % Co, 0.3 wt. % Nb, 0.99 wt. % B and 65.22 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 39 Co 61 The Nb 39 Co 61 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.5%; Alternatively, the neodymium iron boron magnet material is composed of 29.3 wt. % Nd, 0.3 wt. % Pr, 2.3 wt. % Dy, 0.61 wt. % Al, 0.39 wt. % Cu, 0.5 wt. % Co, 0.26 wt. % Nb, 1.01 wt. % B and 65.33 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 33 Co 67 The Nb 33 Co 67 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.3%; Alternatively, the neodymium iron boron magnet material is composed of 30.7 wt. % Nd, 0.1 wt. % Pr, 1.5 wt. % Dy, 1.15 wt. % Al, 0.37 wt. % Cu, 0.6 wt. % Co, 0.25 wt. % Nb, 0.99 wt. % B and 64.34 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 35 Co 65 The Nb 35 Co 65 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.4%; Alternatively, the neodymium iron boron magnet material is composed of 28.9 wt. % Nd, 0.6 wt. % Tb, 0.46 wt. % Al, 0.36 wt. % Cu, 0.5 wt. % Co, 0.26 wt. % Nb, 0.98 wt. % B and 67.94 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 39 Co 61 The Nb 39 Co 61 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.5%; Alternatively, the neodymium iron boron magnet material is composed of 28.3 wt. % Nd, 1.2 wt. % Tb, 0.45 wt. % Al, 0.35 wt. % Cu, 0.5 wt. % Co, 0.26 wt. % Nb, 0.99 wt. % B and 67.95 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 34 Co 66 The Nb 34 Co 66 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.5%; Alternatively, the neodymium iron boron magnet material is composed of 27 wt. % Nd, 0.2 wt. % Pr, 2.5 wt. % Tb, 0.45 wt. % Al, 0.36 wt. % Cu, 0.5 wt. % Co, 0.26 wt. % Nb, 0.99 wt. % B and 67.74 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 35 Co 65 The Nb 35 Co 65 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.4%; Alternatively, the neodymium iron boron magnet material is composed of 27.5 wt. % Nd, 2 wt. % Tb, 0.45 wt. % Al, 0.36 wt. % Cu, 0.6 wt. % Co, 0.26 wt. % Nb, 0.99 wt. % B and 67.84 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 35 Co 65 The Nb 35 Co 65 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.3%; Alternatively, the neodymium iron boron magnet material is composed of 28.3 wt. % Nd, 0.1 wt. % Pr, 0.9 wt. % Dy, 0.7 wt. % Al, 0.42 wt. % Cu, 0.7 wt. % Co, 0.25 wt. % Nb, 0.99 wt. % B and 67.64 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 35 Co 65 The Nb 35 Co 65 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.4%; Alternatively, the neodymium iron boron magnet material is composed of 30.5 wt. % Nd, 1.5 wt. % Dy, 0.65 wt. % Al, 0.45 wt. % Cu, 0.6 wt. % Co, 0.25 wt. % Nb, 0.98 wt. % B and 65.07 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 32 Co 68 The Nb 32 Co 68 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.3%; Alternatively, the neodymium iron boron magnet material is composed of 29.7 wt. % Nd, 1.7 wt. % Dy, 0.61 wt. % Al, 0.4 wt. % Cu, 0.5 wt. % Co, 0.25 wt. % Nb, 0.99 wt. % B and 65.85 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 33 Co 67 The Nb 33 Co 67 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.3%; Alternatively, the neodymium iron boron magnet material is composed of 29.1 wt. % Nd, 1.5 wt. % Tb, 0.46 wt. % Al, 0.37 wt. % Cu, 0.25 wt. % Co, 0.35 wt. % Nb, 0.99 wt. % B and 66.98 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 39 Co 61 The Nb 39 Co 61 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.2%; Alternatively, the neodymium iron boron magnet material is composed of 29.5 wt. % Nd, 0.2 wt. % Dy, 0.8 wt. % Tb, 0.46 wt. % Al, 0.37 wt. % Cu, 0.25 wt. % Co, 0.55 wt. % Nb, 1.04 wt. % B and 66.83 wt. % Fe, where wt. % means the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet material, and the grain boundary phase of the neodymium iron boron magnet material contains Nb. 40 Co 60 The Nb 40 Co 60 The ratio of the area of the grain boundary phase to the total area of the grain boundary phase is 4.1%.
2. The neodymium iron boron magnet material according to claim 1 .
6. A method for producing a neodymium iron boron magnet material, comprising the steps of: The method includes the steps of preparing raw materials of each component according to the components of the neodymium iron boron magnet material according to any one of claims 1 to 3 and 5, and then melting and refining the mixture of the raw materials of each component, casting, crushing, molding, sintering and aging treatment in order; The aging treatment includes a three-stage aging treatment, in which the temperature of the first stage aging treatment is 850 to 950°C, the temperature of the second stage aging treatment is 650 to 700°C, and the temperature of the third stage aging treatment is 450 to 550°C. A method for producing a neodymium iron boron magnet material.
7. The temperature of the first stage aging treatment is 870 to 890°C, And / or, the time of the first stage aging treatment is 2 to 4 hours, And / or, the temperature of the second stage aging treatment is 660 to 690°C, And / or, the time of the second stage aging treatment is 1 to 4 h, And / or the temperature of the third stage aging treatment is 480 to 500°C, And / or, the time of the third stage aging treatment is 1 to 4 h, And / or, after the third stage aging treatment, a grain boundary diffusion treatment is further performed, Here, the temperature of the grain boundary diffusion treatment is 850 to 1000° C. wherein the time for the grain boundary diffusion treatment is 10 to 30 hours; wherein the diffusion source of the grain boundary diffusion treatment is Dy metal powder and / or an alloy containing Dy, and the mass percentage of the diffusion source relative to the total mass of the NdFeB magnet material is 0.3 to 0.5 wt. %; 7. The method for producing a neodymium iron boron magnet material according to claim 6.
8. The vacuum degree of the melting and smelting is 5×10 -2 Pa, And / or, the temperature of the smelting is 1550°C or less, And / or, the casting is performed by rapid solidification casting, and / or the casting temperature is 1390-1460°C; and / or the thickness of the alloy flake obtained after the casting is 0.25 to 0.40 mm; And / or the crushing is performed in the order of hydrocrushing and jet mill crushing, Here, the hydrogen crushing process includes hydrogen absorption, dehydrogenation, and cooling treatment in this order, the hydrogen pressure in the hydrogen absorption is 0.085 MPa, and the dehydrogenation temperature is 480 to 520°C. Here, the gas atmosphere during the jet mill pulverization has an oxidizing gas content of 100 ppm or less, and the gas content means the oxygen and / or moisture content, wherein a lubricant is further added after the jet mill pulverization, the lubricant is zinc stearate, and the amount of the lubricant added is 0.05 to 0.15% of the powder mass obtained after the jet mill pulverization; And / or, the molding is a magnetic field molding, and the magnetic field strength in the magnetic field molding is 1.8 to 2.5 T; and / or the sintering temperature is 1000 to 1100°C; And / or the sintering time is 4 to 8 h; 7. The method for producing a neodymium iron boron magnet material according to claim 6.
9. A neodymium-iron-boron magnet material produced by the method for producing a neodymium-iron-boron magnet material according to claim 6.
Citation Information
Patent Citations
R-Fe-B-Cu-Al-series sintered magnet and preparation method thereof
CN110021466A
R-T-B series permanent magnet material, raw material composition and preparation method and application thereof
CN111613408A
R-T-B series permanent magnet material, raw material composition and preparation method and application thereof
CN111613409A
